Globalisation, liberalisation and the welfare state - Bhambhri, C.P. (1996)
Focusing on uncertainties about State-centred social welfare activity under liberalisation, the author examines nature of State in India and West, impact thereon of level of effluence of its subjects and its indispensability in managing a crisis, and shows that the crucial issue in this regard is the efficiency of State, irrespective of its ideological framework. - Reproduced
Keywords: Liberalization - India; Welfare state - India; Globalization - India; Globalization